The level of Internet usage and its role on democratization among selected states in the Arab region - Ang, Iana L.; De Paz, Mark Jacob Leonido; Del Rosario, Kristine Demilou; Oquendo, Rene Alvin F. (2013)
This study identifies twenty-two (22) selected states located in the Arab Region, namely; Algeria, Bahrain, Comoros, Djobouti, Egypt, Iran, Iraq, Jordan, Kuwait, Lebanon, Libya Arab Jamahiriy, Mauritania, Morocco, Oman, Qatar, Saudi Arabia, Somalia, Sudan, Syrian Ayab Republic, Tunisia, United Arab Emirates, and Yemen. These selected states in the Arab region have caught the attention of the international arena with their struggles for democratization. Those struggles in the region were mainly caused by problems that arose from dictatorial governments or absolute monarchies.
In the advent of technology, Internet usage among citizens is considered to be a tenet of a country's democratization process. Hence, the Arab region is an interesting locale for studying the level of Internet usage and its role on the democratization process. Democratization refers to the process by which countries strive to embrace the overarching principle behind governance which is democracy.
The authors conducted this quantitative study to determine the level of Internet usage of the citizens among selected states in the Arab region and how it affects the democratization process in these countries.
In this study, the researchers found that the level of Internet usage by citizens has weak significance with respect to the democratization process among the selected countries in the Arab region.